Faktor-Faktor yang Mempengaruhi Keputusan Investasi Industri Kecil dan Menengah di Kota Ternate - Rheza Pratama (JUDICIOUS, 2022)
Increased financial literacy and financial attitude can develop small and medium industrial enterprises (IKM) because IKM can understand the basic concepts of financial products, and effective financial planning and management, the right financial attitude also then protects business activities from fraud and improper work. healthy business environment. This study aims to determine the effect of financial literacy and financial attitudes on the investment decisions of SMEs in Ternate City. This study uses a quantitative method approach. The data collection method uses a non-probability sampling technique using a questionnaire. This study uses multiple linear regression analysis using the SPSS program. The results of the determinant coefficient (R2) show a percentage of 61.9% and the remaining 38.1% is explained by other variables. The results of this study can be concluded that financial literacy and financial attitude are factors that influence SMEs in Ternate City actors in making investment decisions. It is expected that further research can develop this research by using other variables which in theory have an influence on investment decisions